Experimental and numerical study of fluidized bed combustion with air staging using palm shell - Rosyida Permatasari, 1966-, author; Mohammad Nazri Mohd. Jaafar, supervisor; Tholudin Mat Lazim, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Thesis (Ph.D (Kejuruteraan Mekanikal)) - Universiti Teknologi Malaysia, 2013